Endothelial Notch signaling directly regulates the small GTPase RND1 to facilitate Notch suppression of endothelial migration - Bhairavi Swaminathan; Seock-Won Youn; L. A. Naiche; Jing Du; Stephanie R. Villa; Jordan B. Metz; Huijuan Feng; Chaolin Zhang; Raphael Kopan; Peter A. Sims; Jan K. Kitajewski (Scientific Reports, 2022)
Abstract To control sprouting angiogenesis, endothelial Notch signaling suppresses tip cell formation, migration, and proliferation while promoting barrier formation. Each of these responses may be regulated by distinct Notch-regulated effectors. Notch activity is highly dynamic in sprouting endothelial cells, while constitutive Notch signaling drives homeostatic endothelial polarization, indicating the need for both rapid and constitutive Notch targets. In contrast to previous screens that focus on genes regulated by constitutively active Notch, we characterized the dynamic response to Notch. We examined transcriptional changes from 1.5 to 6 h after Notch signal activation via ligand-specific or EGTA induction in cultured primary human endothelial cells and neonatal mouse brain. In each combination of endothelial type and Notch manipulation, transcriptomic analysis identified distinct but overlapping sets of rapidly regulated genes and revealed many novel Notch target genes. Among the novel Notch-regulated signaling pathways identified were effectors in GPCR signaling, notably, the constitutively active GTPase RND1. In endothelial cells, RND1 was shown to be a novel direct Notch transcriptional target and required for Notch control of sprouting angiogenesis, endothelial migration, and Ras activity. We conclude that RND1 is directly regulated by endothelial Notch signaling in a rapid fashion in order to suppress endothelial migration.